Nondestructive testing method of SiCp particle dispersion in SiCp/AZ91D magnesium matrix composites - HU Ke; YAO Junping; LU Minghui; CHENG Shuyun; DONG Xingyu (Cailiao gongcheng, 2023)
SiCp/AZ91D magnesium matrix composites are widely used in the aerospace field, but there is less report on the distribution of SiCp particles in SiCp/AZ91D magnesium matrix composites by ultrasonic testing methods at home and abroad. In this paper, SiCp particle reinforced magnesium matrix composites with volume fractions of 0%, 2%, 4% and 6% were prepared by squeeze casting. In order to study the particle distribution in composite materials, ultrasonic velocity method, ultrasonic attenuation method, ultrasonic characteristic scanning imaging method and nonlinear ultrasonic testing method were used to study the dispersion of SiCp particles. The relationship between various acoustic parameters and SiCp volume fraction, and the difference of detection ability of different detection methods for SiCp particle distribution were explored and verified by experiments. The results show that ultrasonic characteristic scanning detection and ultrasonic velocity method can quantitatively detect SiCp macro agglomeration, ultrasonic attenuation method can have a good effect on characterizing both micro agglomeration and macro agglomeration, and nonlinear ultrasonic detection method is more sensitive to detecting SiCp micro agglomeration. When the particles are uneven, the mechanical properties are most affected, and the tensile strength is greatly reduced.